THE ROLE OF SOCIAL CAPITAL IN PROMOTING SUSTAINABLE ORGANIZATIONS: A STUDY OF THE OPINIONS OF A SAMPLE OF ADMINISTRATIVE LEADERS IN A NUMBER OF COLLEGES OF THE UNIVERSITY OF MOSUL - Reem Saad Aljameel (Scholars Digest Publishing, 2025)
Social capital is one of the important topics, and with the racing rates of change in the competition environment in entrepreneurship in organizations, the increasing importance of this topic has become as one of the options that organizations resort to to adapt and suit the requirements of change and creativity in order to achieve precedence and strengthen sustainable organizations, and from this point of view the research aimed to clarify the nature of the relationship between social capital in promoting sustainable organizations, through the adoption of the formula of the relationship of correlation and influence between the two variables. In order to analyse the results of the research sample, which was surveyed by 72 administrative leaders working in various colleges of the University of Mosul, the research relied on a questionnaire that was designed as a measure of the research. Due to the significant impact and strong correlation between the two variables, the research reached important conclusions regarding the existence of sustainable organisations and their effectiveness among administrative leaders who work through the social capital of the organisation surveyed. The research's premise was validated, and several conclusions and recommendations were developed as a result.
Keywords: Social capital / concept and dimensions, sustainable organizations / concept and dimensions.